Perancangan Website SMA Negeri 1 Tanah Masa Baluta Nias dengan Metode System Development Life Cycle - Kurniadin Nehe; Iskandar Fitri; Albaar Rubhasy (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The purpose of this study is to design a web-based information system to provide information about the right SMA Negeri 1 Tanah Masa Baluta Nias, which can be accessed anywhere and used by the wider community and can accelerate up-to-date information about existing educational institutions. in the Tanah Masa Baluta District, Nias Regency, South Nias Regency, North Sumatra Province. This study uses the System Development Life Cycle Method so that you know the strategy or structure of the system that will be designed at the school, so that you can get the best quality website. Based on the results of the discussion on website design for SMA Negeri 1 Tanah Masa Baluta, it can be concluded that the results of the comparison of these methods are 85% in helping information services and management in processing school data more quickly and effectively and making it easier for the public to access information about SMA Negeri 1 Tanah Masa Baluta Nias.